The acoustic designer: Joining soundscape and architectural acoustics in architectural design education. Issue 2 (June 2020) - Milo, Alessia
This article discusses the integration of acoustic design approaches into architectural design education settings. Solving architectural acoustic problems has been for centuries one of the primary aims of theories and experiments in acoustics. Recent contributions offered by the soundscape approach have highlighted broader desirable aims which acoustic designers should pursue, fostering ecological reasoning on the acoustic environment and its perception as a whole. Drawing from the available literature, some examples are brought to show the integration of architectural acoustics and soundscape approaches into the realm of architectural design education, highlighting the significance of specific design situations and aural training techniques in learning contexts.